Crystallization of isodimorphic aliphatic random copolyesters: Pseudo-eutectic behavior and double-crystalline materials. (April 2018) - Pérez-Camargo, Ricardo A.; Arandia, Idoia; Safari, Maryam; Cavallo, Dario; Lotti, Nadia; Soccio, Michelina; Müller, Alejandro J.
Graphical abstract: Abstract: Isodimorphic random copolyesters are intriguing polymeric materials that can crystallize in their entire composition range, despite the random distribution of comonomer units along their chains. This behavior stems from the relatively similar chemical repeating units of the parent homopolymers. In this feature article, we review our recent works on isodimorphic aliphatic copolyesters, and extract general trends in the framework of the literature. Isodimorphic behavior is a complex phenomenon driven by comonomer partition within the crystalline unit cells formed. These copolyesters crystallize in the entire composition range displaying a pseudo-eutectic behavior when their melting points are plotted as a function of composition. Two crystalline phases, which resembled the crystalline structures of the parent homopolymers, are formed, depending on the considered composition range. The unit cell dimensions of the parent homopolymers change, as a consequence of the inclusion of co-units. At the pseudo eutectic point or pseudo-eutectic region, two crystalline phases can co-exist and their formation strongly depends on thermal history. In this case, double crystalline random copolyesters with two melting points and mixed double-crystalline spherulites can be obtained. The exact composition of the pseudo-eutectic point, the level of comonomer inclusion and the crystallinity degrees cannot be easily predicted by the copolyester chemical structure and composition. These are important issues for further future studies, as well as the quantitative determination of comonomer inclusion in the generated crystalline phases. The extraordinary variation of thermal properties, morphology and crystallinity that isodimorphic random copolyesters display as a function of composition, allows to conveniently tailor their biodegradation, permeability to gases and mechanical properties.